Pemetaan Sumber Daya Hutan Kawasan TAHURA KGPAA Mangkunagoro I di Desa Wonorejo Kecamatan Jatiyoso Kabupaten Karanganyar - Afandi, Muslim; Fahruzzaman, Fahruzzaman (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2026)
Community interactions within the buffer zone of the KGPAA Mangkunagoro I Grand Forest Park (TAHURA) reflect deep interdependence between forest ecosystems and local livelihoods. Grounded in the ecosystem services framework, this study aims to map forest resource governance in Wonorejo Village, Jatiyoso Sub-district, Karanganyar Regency, which has undergone a land-use transition from Perhutani to TAHURA jurisdiction. Using a Participatory Learning and Action (PLA) approach, data were collected through Participatory Rural Appraisal (PRA) techniques—including seasonal calendars, trend-and-change analysis, social mapping, and daily expenditure surveys. Results indicate that the forest's primary environmental services encompass freshwater provision, landscape-based tourism, and carbon sequestration, with an estimated total economic value of Rp 540,620,000 per year. Key challenges identified include declining spring water discharge due to inadequate conservation measures, reduced agricultural productivity, and underdeveloped tourism governance. Stakeholder analysis reveals that effective multi-actor collaboration spanning TAHURA management, community groups (LMDH, P3A, POKDARWIS), and local government is essential for sustainable natural resource management. These findings underscore the need for an integrated approach that reconciles ecological conservation with community economic well-being.